A Study of Some Blood Picture Parameters during Experimental Infection with Eimeria tenella in Local breeds and Foreign of Chicken - K. A., Dawood; K. T, AL-Shaibany (Al-Qadisiyah Journal of Pure Science, 2018)
The study was conducted in Animal house of the department of Biology, College of Education, Al-Qadisiya University during the period from 1/9/2013 to 1/9/2014. The study diagnosed the parasite of E.tenella in naturally infected chickens in poultry farms. E.tenella was isolated from the infected cases in Vet. hospital and Vet. clinics.Then,the cases diagnosed initially in the laboratory direct examining stool by ordinary microscope and the positive cases were recorded and diagnosed by using the technique of Conventional Polymerase Chain Reaction(PCR). There are 315 cases of infected chicken which are examined and the results showed that (186 out of 315) stool Samples,59%, The experimental infection for each experiment was done in age 21 day with dosage of (5Ã—104) grown oocysts/chicken for E.tenella in two types of chickens(Ross and local breed) Also,two groups of uninfected chickens (control) are used for the sake of comparison. Hematological parameters in Ross chickens showed significant decrease (p<0.05) in fourth week of infection), percentage of Packed cell volume (PCV)(18.47% in the fifth week of infection) and Red blood cell (RBC) count was (1.58x106 in the fourth week of infection) . Also , the infection led to significant difference of white blood cell (WBC) count (30.19x103 in the seventh week of infection) comparison of uninfected chickens of the control group. While The hematological parameters in local breed showed significant decrease (p<0.05) in Hb concentration and percentage of PCV (7.13mg/100ml , 21.26% respectively in the fifth week of infection) , while the RBC count was (2.05 x 106 in the fourth week of infection and significant increased (p<0.05) in WBC count was (30.63 x 106 the sixth week of infection) in comparison with the chickens of the control group.